MODEL PERENCANAAN PEMBANGUNAN BERBASIS KALO SARA DAN PENGARUHNYA TERHADAP PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA - Syaifudin Suhri Kasim; Sarmadan Sarmadan; Ratna Supiyah; Damsid Damsid (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2022)
This study aims to determine how the process of implementing the Kalo sara-based village development planning model is and its effect on increasing community participation in village development in Lambudoni Village, Andowia District, North Konawe Regency. Informants were selected with purposive sampling. The selected informants included: village head, village secretary, head or BPD member, traditional leaders and several local residents. Using a qualitative descriptive method, the data was collected through observation, interviews and documentation. Data analysis was carried out using a qualitative descriptive method. The results show that the process of implementing Kalo sara-based village development planning started with the hamlet level for them to discuss what the main problems are in the area and the results are formulated in the form of a village development program. Thereafter, the results of the program formulation are then brought to the sub-district level to be discussed by the sub-district government along with residents and village officials, and the results are formulated into 2 (two) program priorities: main priority; and (2) supporting priority development programs. Kalo sara influences very significantly the level of community participation in village development because it contains the values ​​of samaturu (mutual cooperation); medulu mepokoso (unity and integrity); ate pute penao moroha (holiness and justice); and morini mbu'umbudi monapa mbu'undawaro (prosperity and welfare) that become the spirit or motivation for the community to keep participating actively in each of village development plans.